ESTIMACIÓN DE LLUVIAS MENSUALES DURANTE EL EVENTO EL NIÑO DÉBIL A MODERADO 2002 - Fashé Raymundo, O. (2005)
The main objective of this paper is to estímate the monthly rainfall over Peru during EL NIÑO weak to moderate of the 2002 year. To make this GOES-8 satellite images and the convective stratiform technique are used. An analysis of the comparison between GOES-8 estimates and monthly rainfall gauges values is presented. It is observed that the monthly rain rate estímate over the Peruvian rain forest offers the best correlations. However the Peruvian mountain presents the mínimum bias. An explanation is developed to these results making an analysis of the estimates of rain rate that diverse authors carry out in other latitudes.